Axial compressive behavior on steel tube-retrofitted circular RC short columns with grout under preload. (October 2021) - Hu, Xiao; Chen, Zhenlin; Bu, Xiangbo
Abstract: Steel tubes are widely used in strengthening reinforced concrete (RC) columns. However, in engineering construction, the effect of preload on the original RC column on the performance of strengthened RC column has not mostly considered. Therefore this paper tests five circular short columns under axial compression—three steel tube-strengthened RC columns with preload, one strengthened RC column with no preload, and one normal RC-to study compressive performance of steel tube-retrofitted circular RC short columns under various preload levels. Moreover, the verified finite element numerical model is established using ABAQUS software to stimulate the behavior of the retrofitted columns. The extended parametric studies is conducted based on the thickness of steel tube, yield strength of steel tube, and strength of grout under preload, in addition to preload level itself. A practical design method is proposed and compared with four existing design codes to predict the axial compressive ultimate strength of the retrofitted column under preload.